2013
DOI: 10.1002/art.38188
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐127‐5p Regulates Matrix Metalloproteinase 13 Expression and Interleukin‐1β–Induced Catabolic Effects in Human Chondrocytes

Abstract: Objective. MicroRNAs (miRNAs), small noncoding RNA molecules, are involved in the pathogenesis of various diseases such as cancer and arthritis. The aim of this study was to determine whether miR-127-5p regulates interleukin-1␤ (IL-1␤)-induced expression of matrix metalloproteinase 13 (MMP-13) and other catabolic factors in human chondrocytes.Methods. Expression of miR-127-5p and MMP-13 by normal and osteoarthritic (OA) human cartilage was determined using real-time polymerase chain reaction. The effect of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 39 publications
(47 reference statements)
2
78
0
1
Order By: Relevance
“…MiR-127 expression is reduced in knee OA AC compared to normal AC [190,191]. Increased MMP-13 expression upon rIL-1β treatment in monolayer cell cultures of human OA AC correlated with miR-127 suppression, with MMP-13 as a direct target of miR-127.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-127 expression is reduced in knee OA AC compared to normal AC [190,191]. Increased MMP-13 expression upon rIL-1β treatment in monolayer cell cultures of human OA AC correlated with miR-127 suppression, with MMP-13 as a direct target of miR-127.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…Increased MMP-13 expression upon rIL-1β treatment in monolayer cell cultures of human OA AC correlated with miR-127 suppression, with MMP-13 as a direct target of miR-127. In addition, miR-127 inhibits also MMP-1 expression in response to rIL-1β [190]. Collectively, with downregulation of miR-127 in OA AC, another anti-catabolic miRNA in AC is disenabled.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…The activity of MMP-13 can be regulated at multiple levels, which include transcriptional regulation [26], epigenetic modification [27], post-transcriptional regulation by microRNAs [28], [29], [30], activation of pro-enzymes [9], [10] and inhibition by endogenous inhibitors [9], [10]. In addition, Partridge and co-workers have shown that rat MMP-13 is endocytosed and degraded by osteoblastic cells [31] and this requires a two-step processes, involving a first binding to a 170 kDa cell surface receptor with a high-affinity and it is subsequently endocytosed through low-density lipoprotein (LDL) receptor-related protein 1 (LRP1) [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing data show that IL-1-induced chondrocyte responses represent central pathogenic events in RA and osteoarthritis [26,28] . IL-1 in vitro directly inhibits cartilage proteoglycan synthesis and chondrocyte proliferation [29] .…”
Section: Ast Protects Against Il-1-suppressed Cartilage Proteoglycanmentioning
confidence: 99%